Lidando com o inimigo: caracterização comportamental, molecular e cardiovascular de roedores resilientes e susceptíveis ao estresse de derrota social - Silva, Gessynger Morais (Universidade Federal de São Carlos, 2021)
Despite the well-known correlation between prolonged stress and the development of diseases, not every individual exposed to stressful situations develops stress-related disorders. This individual difference could be related to their ability to cope with the adverse events, that is, their resilience or susceptibility to the stress. In the context, this work aimed to evaluate the differences between the resilient and susceptible phenotypes in an animal model of psychosocial stress exposure. In the chapter 1, we evaluated the behavioral, molecular and cardiovascular differences in the resilient and susceptible phenotypes to the social defeat stress (SDS) in rats, and the effect of the N-Acetylcysteine (N-AC) treatment in such alterations. In the chapter 2, we evaluated the role of the ventral pallidum Npas1+ neurons in the susceptibility to the SDS in mice. Using the repeated SDS exposure followed by the social interaction test (SIT), we identified Wistar rats as resilient or susceptible to the SDS in the chapter 1. The susceptible rats showed social avoidance, depressive-like behavioral alterations, long-term memory impairment and cardiovascular alterations related to the development of cardiovascular diseases. Except for memory impairment, resilient rats did not develop the alterations found in the susceptible phenotype, in addition to show cardiovascular alterations related to a protective effect from the stress consequences in the cardiovascular system. These two phenotypes showed distinct alterations in the expression of DeltaFosB and the cystine-glutamate exchanger in the brain. The N-AC treatment reverted the depressive-like behavioral alterations in the susceptible rats to the SDS, but did not altered the DeltaFosB expression related to the stress-coping phenotypes. In the chapter 2, we verified that the activation of the ventral pallidum Npas1+ neurons increased the susceptibility to the SDS in mice, in addition to increase the anxiety-like behaviors. These neurons projects to diverse encephalic areas important in the stress-response, especially the nucleus accumbens, ventral tegmental area and lateral habenula. In conclusion, susceptible rats to the SDS showed numerous behavioral and cardiovascular alterations after repeated stress exposure, which are absent in the resilient rats. Such alterations seem to be related to DeltaFosB expression in brain areas related to stress-response. The N-AC treatment in able to revert the behavioral alterations, besides not being effective to change the neuronal molecular alterations related to stress exposure. The SDS susceptibility could be related to the activity of the ventral pallidum Npas1+ neurons, since their activation increased the SDS susceptibility in mice.
Dealing with the enemy: behavioral, molecular and cardiovascular characterization of resilient and susceptible rodents to the social defeat stress
Keywords: Estresse de derrota social; Resiliência; Susceptibilidade; Depressão; N-acetilcisteína; DeltafosB; Social defeat stress; Resilience; Susceptibility; Depression; N-acetylcysteine; CIENCIAS BIOLOGICAS::FARMACOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS::FARMACOLOGIA::NEUROPSICOFARMACOLOGIA